Squalene epoxidase as a promising metabolic target in cancer treatment. (1st July 2018) - Cirmena, Gabriella; Franceschelli, Paola; Isnaldi, Edoardo; Ferrando, Lorenzo; De Mariano, Marilena; Ballestrero, Alberto; Zoppoli, Gabriele
Abstract: Oncogenic alteration of the cholesterol synthesis pathway is a recognized mechanism of metabolic adaptation. In the present review, we focus on squalene epoxidase (SE), one of the two rate-limiting enzymes in cholesterol synthesis, retracing its history since its discovery as an antimycotic target to its description as an emerging metabolic oncogene by amplification with clinical relevance in cancer. We review the published literature assessing the association between SE over-expression and poor prognosis in this disease. We assess the works demonstrating how SE promotes tumor cell proliferation and migration, and displaying evidence of cancer cell demise in presence of human SE inhibitors in in vitro and in vivo models. Taken together, robust scientific evidence has by now accumulated pointing out SE as a promising novel therapeutic target in cancer treatment. Highlights: Squalene epoxidase (SE) plays a critical role in cholesterol metabolism, which is recognized for its relevance in cancer. SE copy number gain and overexpression have been associated with tumor occurrence, development and poor prognosis. SE blockade causes human cancer cell demise, pointing towards a novel and promising therapeutic strategy in cancers.